2023
DOI: 10.1017/s136898002300174x
|View full text |Cite
|
Sign up to set email alerts
|

Development of an initiatives package to increase children’s vegetable intake in long day care centres using the Multiphase Optimisation Strategy (MOST) randomised factorial experiment

Lucinda K Bell,
Samantha Morgillo,
Dorota Zarnowiecki
et al.

Abstract: Objective: To inform a package of initiatives to increase children’s vegetable intake while in long day care (LDC) by evaluating the independent and combined effects of three initiatives targeting food provision, the mealtime environment, and the curriculum. Design: Using the Multiphase Optimisation Strategy (MOST) framework, a 12-week, eight-condition (n=7 intervention, n=1 control) randomised factorial experiment was conducted. Children’s dietary intake data was measured pre- and post-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
11
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(11 citation statements)
references
References 29 publications
0
11
0
Order By: Relevance
“…Centres were eligible to participate if they were: (1) LDC centres located in Australia who operate for at least 8 hours per weekday (Monday to Friday), (2) care for children aged 2–5 years, (3) are responsible for the centre menu planning and (4) prepare food onsite serving lunch and two between-meal snacks each day (morning and afternoon). Centres were excluded if they catered exclusively to children with special needs or if they participated in the previous optimisation study ( 20 ) . Within centres, children aged 2–5 years were eligible.…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…Centres were eligible to participate if they were: (1) LDC centres located in Australia who operate for at least 8 hours per weekday (Monday to Friday), (2) care for children aged 2–5 years, (3) are responsible for the centre menu planning and (4) prepare food onsite serving lunch and two between-meal snacks each day (morning and afternoon). Centres were excluded if they catered exclusively to children with special needs or if they participated in the previous optimisation study ( 20 ) . Within centres, children aged 2–5 years were eligible.…”
Section: Methodsmentioning
confidence: 99%
“…The MOST framework uses a cyclic approach and comprises three phases: (1) Preparation, (2) Optimisation and (3) Evaluation ( 18 ) . Using this framework, we previously developed three initiatives to increase children’s vegetable intake in LDC: (1) Food provision, (2) Mealtime environment and (3) Curriculum ( 19 ) (preparation phase) and tested them using an eight-group factorial trial to determine the most efficient intervention (optimisation phase) ( 20 ) . We found that the Mealtime environment with Curriculum initiative combination had the most promise for increasing children’s vegetable intake ( 20 ) .…”
mentioning
confidence: 99%
See 3 more Smart Citations